Complex traveling-wave and solitons solutions to the Klein-Gordon-Zakharov equations - Houwe, Alphonse; Abbagari, Souleymanou; Salathiel, Yakada; İnç, Mustafa; Doka, Serge Y.; Crepin, Kofane Timoleon; Baleanu, Dumitru (Elsevier, 2020)
This paper studies complex solutions and solitons solutions to the Klein-Gordon-Zakharov equations (KGZEs). Solitons solutions including bright, dark, W-shape bright, breather also trigonometric function solutions and singular solutions of KGZEs are obtained by three integration algorithm. From the spatio-temporal and 3-D and 2-D contour plot, it is observed that obtained solutions move without any deformation that implies the steady state of solutions. Furthermore, these solutions will be helpful to explain the interactions in hight frequency plasma and solitary wave theory.
Keywords: Solitary waves; KGZEs; W-shape soliton